2009
DOI: 10.1021/nl8037807
|View full text |Cite
|
Sign up to set email alerts
|

Two-Terminal Nanoelectromechanical Devices Based on Germanium Nanowires

Abstract: A two-terminal bistable device, having both ON and OFF regimes, has been demonstrated with Ge nanowires using an in situ TEM-STM technique. The function of the device is based on delicately balancing electrostatic, elastic, and adhesion forces between the nanowires and the contacts, which can be controlled by the applied voltage. The operation and failure conditions of the bistable device were investigated, i.e. the influence of nanowire diameter, the surface oxide layer on the nanowires and the current densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
95
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(96 citation statements)
references
References 48 publications
0
95
0
1
Order By: Relevance
“…The I − V curve shown in Figure 3c shows a nonvolatile switching behavior with a threshold voltage of 46.5 V, which is higher than other reported Ge-based devices 21 and carbonnanotube-based electromechanical switches 20 . Upon switching to the 'on state', an Ohmic contact between the two Cu wires was observed with an overall contact resistance measured to bẽ 2.0 MΩ.…”
Section: Results and Discussion Manufacturing 3d Cu Microswitches On mentioning
confidence: 62%
See 1 more Smart Citation
“…The I − V curve shown in Figure 3c shows a nonvolatile switching behavior with a threshold voltage of 46.5 V, which is higher than other reported Ge-based devices 21 and carbonnanotube-based electromechanical switches 20 . Upon switching to the 'on state', an Ohmic contact between the two Cu wires was observed with an overall contact resistance measured to bẽ 2.0 MΩ.…”
Section: Results and Discussion Manufacturing 3d Cu Microswitches On mentioning
confidence: 62%
“…Recently, Jang et al 8,20 demonstrated a vertical, three-terminal, carbon-nanotube-based electromechanical switch, in which multiwalled carbon nanotubes were catalytically grown and used as active elements. Similarly, free-standing germanium nanowires 21,22 and Mo 6 S 3 I 6 nanowires 23 were also used as switching elements. Although such microswitches provide many advantages compared with conventional semiconductor switches and are being studied in detail [24][25][26][27] , most of those fabrications are incompatible with typical microfabrication processes.…”
Section: Introductionmentioning
confidence: 99%
“…12 Recently, in-situ techniques were also used to characterize the electrical performance of Germanium (Ge) nanowires 13 and MWNTs 14 that were physically welded or connected to the ends of metallic probe tips for NEMS applications. In our work on 3D NEMS, we have examined the nanomechanical properties of the tubes using in situ techniques which are described in Section 3.2.…”
Section: Nems Switch Topologiesmentioning
confidence: 99%
“…Нитевидные наноструктуры Ge благодаря своим элек-трофизическим и оптическим свойствам имеют широкий спектр применения: в литий-ионных аккумуляторах [1], фотовольтаике [2], устройствах памяти [3], оптике [4], наноэлектромеханических системах [5]. Для формиро-вания полупроводниковых нанонитей Ge в основном используется газофазное осаждение [6].…”
Section: Introductionunclassified